2020
DOI: 10.1136/tsaco-2020-000512
|View full text |Cite
|
Sign up to set email alerts
|

Long-term patient-reported outcome measures after injury: National Trauma Research Action Plan (NTRAP) scoping review protocol

Abstract: BackgroundA significant proportion of patients who survive traumatic injury continue to suffer impaired functional status and increased mortality long after discharge. However, despite the need to improve long-term outcomes, trauma registries in the USA do not collect data on outcomes or care processes after discharge. One of the main barriers is the lack of consensus regarding the optimal outcome metrics.ObjectivesTo describe the methodology of a scoping review evaluating current evidence on the available mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 17 publications
0
19
0
Order By: Relevance
“…This finding further supports the NTRAP's emphasis on patient-reported outcomes (PROs) and the identification of outcome measures that are best fit for each group of patients, PRO measures (PROMS). In a scoping review of 747 research articles, the NTRAP investigator group found a large number of PROMS for measuring PROs after injury, but efforts to comprehensively understand the health outcomes of trauma patients are insufficient 34 . The lack of consensus on a defined set of PROs at the national level creates inconsistencies in establishing benchmarks for measuring outcomes across institutions and various injury types 34 .…”
Section: Discussionmentioning
confidence: 99%
“…This finding further supports the NTRAP's emphasis on patient-reported outcomes (PROs) and the identification of outcome measures that are best fit for each group of patients, PRO measures (PROMS). In a scoping review of 747 research articles, the NTRAP investigator group found a large number of PROMS for measuring PROs after injury, but efforts to comprehensively understand the health outcomes of trauma patients are insufficient 34 . The lack of consensus on a defined set of PROs at the national level creates inconsistencies in establishing benchmarks for measuring outcomes across institutions and various injury types 34 .…”
Section: Discussionmentioning
confidence: 99%
“…This scoping review is not without limitations and must be interpreted in the context of its design. This study began as a subset analysis from a broader systematic review 16 that included literature on long-term outcome assessment for all types of physical injury. This factor may have reduced the specificity of the search strategy.…”
Section: Discussionmentioning
confidence: 99%
“…The final protocol was published and made available online on May 28, 2020 in Trauma Surgery & Acute Care Open journal ( https://tsaco.bmj.com/content/5/1/e000512 ). 16 The protocol was disseminated through the Coalition for National Trauma Research twitter account (@NatTrauma).…”
Section: Methodsmentioning
confidence: 99%